Pengaruh Kompensasi, Disiplin Kerja, Dan Motivasi Kerja Terhadap Produktivitas Karyawan CV. Putra Tunggal Kabupaten Gresik - Sakinah, Safira Syafa’atus; Nurhidayah, Nurhidayah; Mustapita, Arini Fitria (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract Human resources (HR) is very important in a company. The success of a company to achieve its goals is determined by the productivity of its employees. Every company must be able to maintain and improve the quality of the performance of its human resources. A good company will certainly pay attention to the needs of its employees so that employees are comfortable working. If employees feel their needs are met, employees will automatically do more than the company expects so that employee productivity will be assessed as good by the company. A good company will certainly pay attention to the needs of its employees so that employees are comfortable working by looking at how their compensation, work discipline and work motivation are. This study aims to determine the effect of employee productivity from compensation, work discipline, and work motivation at CV. Only Son. This study uses multiple linear regression analysis. The results of this study are that the compensation variable has an insignificant effect. On the work discipline variable there is an insignificant effect. On the variable work motivation there is a significant influence. Keywords : compensation, work discipline, work motivation, work productivity